2009
DOI: 10.1183/09031936.00049509
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic training reverses airway inflammation and remodelling in an asthma murine model

Abstract: Aerobic training (AT) decreases dyspnoea and exercise-induced bronchospasm, and improves aerobic capacity and quality of life; however, the mechanisms for such benefits remain poorly understood. The aim of the present study was to evaluate the AT effects in a chronic model of allergic lung inflammation in mice after the establishment of airway inflammation and remodelling.Mice were divided into the control group, AT group, ovalbumin (OVA) group or OVA+AT group and exposed to saline or OVA. AT was started on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
82
0
20

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(104 citation statements)
references
References 38 publications
(61 reference statements)
2
82
0
20
Order By: Relevance
“…results suggest that a small amount of physical activity is able to effect a significant reduction in BHR; this could then be added to the growing list of already-known benefits of exercise. Using an experimental model of asthma, an intriguing study by Silva et al 28 showed that physical training can reverse airway inflammation and remodeling and improve respiratory mechanics, consequently reducing BHR. 28 If confirmed, these encouraging results could contribute to the development of programs for the primary prevention of lung disease.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…results suggest that a small amount of physical activity is able to effect a significant reduction in BHR; this could then be added to the growing list of already-known benefits of exercise. Using an experimental model of asthma, an intriguing study by Silva et al 28 showed that physical training can reverse airway inflammation and remodeling and improve respiratory mechanics, consequently reducing BHR. 28 If confirmed, these encouraging results could contribute to the development of programs for the primary prevention of lung disease.…”
Section: Allergy Skin Testingmentioning
confidence: 99%
“…People with asthma will increase in levels of T-helper-2 (Th-2) cytokines and undergo chronic airway inflammation and remodeling (Matt et al 2009, Silva et al 2010, Zhang et al 2011. In that condition mast cells develop to an effector phase and produce Th2 cytokines, like IL-4, IL-5, and IL-9.…”
Section: Introductionmentioning
confidence: 99%
“…In this direction, since 2004 a growing number of experimental studies using mouse models of chronic allergic airway inflammation have demonstrated that low and moderate intensity aerobic exercise performed either before, during or after the allergen sensitization results in decreased eosinophilic inflammation, Th2 cytokines production, airway remodeling and hyperresponsiveness [16][17][18][19][20][21][22][23][24]. Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%
“…Shortly, these studies have demonstrated that these beneficial effects can be attributed to decreased activation of leukocytes and bronchial epithelial cells as a result of increased activation of glucocorticoids receptors, T-regulatory cells resulting in increased synthesis of anti-inflammatory cytokine IL-10, and decreased activation of transcriptional factor NF-kB [16][17][18][19][20][21][22][23][24]. In addition, these studies also demonstrated that aerobic exercise present a direct inhibitory effect on the pulmonary oxidants production as well as on the synthesis of mediators involved in the airway remodeling process [19,24].…”
mentioning
confidence: 99%